2016
DOI: 10.3354/esr00767
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective of fragmentation on a declining taxon—the sturgeon (Acipenseriformes)

Abstract: Acipenseriformes (sturgeons and paddlefishes) are considered to be one of the most globally imperiled taxon, with 25 of the 27 species listed by the International Union for the Conservation of Nature (IUCN). Overharvest, habitat degradation, fragmentation and water quality issues have contributed to their decline worldwide. These stressors have been ameliorated in some areas, but in others they remain a limiting factor to sturgeon. Barriers impeding upstream migrations to natural spawning areas and manifesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Of course, temperate eels are not the only species endangered by global change and most diadromous fishes have undergone severe declines (Limburg & Waldman, ; McDowall, ; Mota et al., ). The effects of fragmentation (Haxton & Cano, ; Larinier, ; Limburg & Waldman, ), global warming (Elliott & Elliott, ; Friedland, ; Friedland, Hansen, Dunkley, & MacLean, ; Jonsson & Jonsson, ; Lassalle, Béguer, Beaulaton, & Rochard, ; Lassalle et al., ; Rougier et al., ), fisheries and pollution (Limburg & Waldman, ; McDowall, ) have been documented for most of these species. More generally, most migratory animals regardless of taxa have undergone similar declines (Berger, Young, & Berger, ; Sanderson, Donald, Pain, Burfield, & van Bommel, ; Wilcove & Wikelski, ) raising the question of sustainability of migratory tactics in the face of global change.…”
Section: Other Implications For Eel Management and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, temperate eels are not the only species endangered by global change and most diadromous fishes have undergone severe declines (Limburg & Waldman, ; McDowall, ; Mota et al., ). The effects of fragmentation (Haxton & Cano, ; Larinier, ; Limburg & Waldman, ), global warming (Elliott & Elliott, ; Friedland, ; Friedland, Hansen, Dunkley, & MacLean, ; Jonsson & Jonsson, ; Lassalle, Béguer, Beaulaton, & Rochard, ; Lassalle et al., ; Rougier et al., ), fisheries and pollution (Limburg & Waldman, ; McDowall, ) have been documented for most of these species. More generally, most migratory animals regardless of taxa have undergone similar declines (Berger, Young, & Berger, ; Sanderson, Donald, Pain, Burfield, & van Bommel, ; Wilcove & Wikelski, ) raising the question of sustainability of migratory tactics in the face of global change.…”
Section: Other Implications For Eel Management and Researchmentioning
confidence: 99%
“…Another component is the modification of habitats due to anthropogenic land use, which can lead to fragmentation of aquatic and terrestrial ecosystems or even habitat loss (Brook, Sodhi, & Bradshaw, ; Collinge, ; Fischer & Lindenmayer, ). Habitat loss and ecosystem fragmentation are currently considered major threats to biodiversity and represent one of the major challenges in ecosystem conservation and restoration (Sutherland et al., ; Tilman, May, Lehman, & Nowak, ; Tischendorf & Fahrig, , ), by impairing the ability of individuals to migrate to essential habitats (Gros & Prouzet, ), by isolating populations and reducing gene flow (Haxton & Cano, ; Horreo et al., ), and by modifying species community structure (Perkin & Gido, ). Fragmentation and habitat loss increase the risk of extinction cascades (Fischer & Lindenmayer, ; Haddad et al., ; Junge, Museth, Hindar, Kraabøl, & Vøllestad, ; Krauss et al., ; van Leeuwen, Museth, Sandlund, Qvenild, & Vøllestad, ; Terborgh et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The Acipenseriformes are a primitive order of megafuanal bony fishes comprising the paddlefishes (Polyodontidae) and sturgeons (Acipenseridae). This group of species is considered the most frequently imperilled with extinction (Haxton and Cano ), and 25 of the 27 sturgeon species are listed by the International Union for the Conservation of Nature (IUCN). Imperilment of sturgeons has predominantly been associated with habitat fragmentation, which restricts the ability of sturgeons to migrate to spawning grounds (Birstein et al.…”
mentioning
confidence: 99%
“…A population model of the European sturgeon indicated that fishing mortalities as low as 5% can reduce previously undisturbed populations to no more than 20%–30% of their historic spawning biomass, mainly at the expense of older age‐classes (Jarić & Gessner, ). Reliable longevity estimates require access to undisturbed sturgeon populations, which are rare (Haxton & Cano, ; Jarić & Gačić, ). Longevity is also dependent upon the latitude, with more northern ranges being characterized by a delayed maturity and longer lifespans.…”
Section: Resultsmentioning
confidence: 99%